Chronically altered ventricular activation causes pro-arrhythmic cardiac electrical remodelling in the chronic AV block dog model. Issue 2 (20th September 2022) - van Weperen, Valerie Y H; ter Horst, Iris; Dunnink, Albert; Bossu, Alexandre; Salden, Odette A; Beekman, Henriette D M; Oros, Avram; Bourgonje, Vincent; Stams, Thom; Meine, Mathias; Vos, Marc A
Abstract: Aims: Altered ventricular activation (AVA) causes intraventricular mechanical dyssynchrony (MD) and impedes contraction, promoting pro-arrhythmic electrical remodelling in the chronic atrioventricular block (CAVB) dog. We aimed to study arrhythmogenic and electromechanical outcomes of different degrees of AVA. Methods and results: Following atrioventricular block, AVA was established through idioventricular rhythm (IVR; n = 29), right ventricular apex (RVA; n = 12) pacing or biventricular pacing [cardiac resynchronization therapy (CRT); n = 10]. After ≥3 weeks of bradycardic remodelling, Torsade de Pointes arrhythmia (TdP) inducibility, defined as ≥3 TdP/10 min, was tested with specific IKr -blocker dofetilide (25 μg/kg/5 min). Mechanical dyssynchrony was assessed by echocardiography as time-to-peak (TTP) of left ventricular (LV) free-wall minus septum (ΔTTP). Electrical intraventricular dyssynchrony was assessed as slope of regression line correlating intraventricular LV activation time (AT) and activation recovery interval (ARI). Under sinus rhythm, contraction occurred synchronous (ΔTTP: −8.6 ± 28.9 ms), and latest activated regions seemingly had slightly longer repolarization (AT–ARI slope: −0.4). Acute AV block increased MD in all groups, but following ≥3 weeks of remodelling IVR animals became significantly more TdP inducible (19/29 IVR vs. 5/12 RVA and 2/10 CRT, both P < 0.05 vs. IVR). After chronic AVA, intraventricular MD was lowest in CRT animals (ΔTTP: −8.5 ± 31.2 vs. 55.80 ± 20.0 and 82.7 ± 106.2 ms in CRT, IVR, and RVA, respectively, P < 0.05 RVA vs. CRT). Although dofetilide steepened negative AT–ARI slope in all groups, this heterogeneity in dofetilide-induced ARI prolongation seemed least pronounced in CRT animals (slope to −0.8, −3.2 and −4.5 in CRT, IVR and RVA, respectively). Conclusion: Severity of intraventricular MD affects the extent of electrical remodelling and pro-arrhythmic outcome in the CAVB dog model. Graphical Abstract: Graphical Abstract After complete atrioventricular block, chronic atrioventricular block (CAVB) dogs were exposed to different extents of altered ventricular remodelling. Animals either remodelled under idioventricular rhythm (IVR), right ventricular apex (RVA) pacing or cardiac resynchronization therapy (CRT). After remodelling, mechanical dyssynchrony was assessed using echocardiography as difference in time-to-peak (TTP) of left ventricular (LV) free-wall and LV septum. Dofetilide was also administered to assess Torsade de Pointes arrhythmia (TdP) inducibility and dofetilide-induced activation recovery interval (ARI) prolongation. Severity of intraventricular mechanical dyssychrony was shown to affect the extent of electrical remodelling and pro-arrhythmic outcome in the CAVB dog model.